TRADISI PERANG PANDAN SEBAGAI EKSPRESI RELIGIUS, SIMBOLIK, DAN SOSIAL MASYARAKAT BALI AGA TENGANAN - Ni Ketut Riska Dewi Prawita; I Wayan Putra Adi Subawa; Gede Sudha Cahyana; Gede Bagus Wira Diputra; I Gusti Agung Paramita (Pascasarjana Universitas Hindu Indonesia, 2026)
The Pandan War (Mekare-Kare) tradition in Tenganan Pegringsingan Traditional Village, Bali, is one of the cultural heritages of Bali Aga that is rich in religious, symbolic, aesthetic, and social meanings. This study aims to describe the form and stages of the Pandan War tradition, analyze the symbolic meanings, and reveal its role in preserving the cultural identity of the Tenganan community. The research method used a descriptive qualitative approach with data collection techniques in the form of literature studies, interviews, and documentation. The findings show that the Pandan War is not merely a physical battle, but a sacred offering (yadnya) to the God Indra. The symbols used, such as thorny pandan leaves, gringsing cloth, selonding gamelan, and the megibung procession, contain spiritual messages about courage, sacrifice, solidarity, and harmony in life. From a social perspective, this ritual functions to strengthen community cohesion, become a means of traditional education through the Metruna ceremony, and reinforce the collective identity of the Bali Aga amid modernization. Thus, the Pandan War can be understood as a “cultural text” within the framework of Clifford Geertz's symbolic interactionism, which not only preserves the heritage of the ancestors but also strengthens the position of the Tenganan community in the dynamics of global culture.